The Factors Influencing Managerial Performance and their Effect on Financial Accountability - Kawatu, Freddy Semuel; Kewo, Cecilia Lelly (International Journal of Economics and Financial Issues, 2019)
This study aims to examine and analyze the factors that influence managerial performance and their effect for financial accountability. By using an explanatory research method, this type of research is descriptive verification. Using primary data through surveys by providing research instruments to regional work unit tools at North Sulawesi. The collected data tested using the Structural Equation Model (SEM) method with Partial Least Square (PLS) approach. Simultaneous results of participatory budgeting, clarity of budget targets and internal control have a positive effect on managerial performance. Likewise managerial performance has a positive effect on financial accountability. Keywords: Participatory budgeting, Budget goal clarity, Internal control, Managerial performance, financial Accountability JEL Classifications: M41, H70, G38 DOI: https://doi.org/10.32479/ijefi.8551